2008
DOI: 10.1093/nar/gkn600
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stringency wash of partially hybridized 60-mer probes reveals that the stringency along the probe decreases with distance from the microarray surface

Abstract: Here, we describe a multi-parametric study of DNA hybridization to probes with 20–70% G + C content. Probes were designed towards 71 different sites/mutations in the phenylalanine hydroxylase gene. Seven probe lengths, three spacer lengths and six stringencies were systematically varied. The three spacer lengths were obtained by placing the gene-specific sequence in discrete steps along the 60-mer probes. The study was performed using Agilent 8 × 15 000 probes custom-made arrays and a home-built array washer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 55 publications
1
44
1
Order By: Relevance
“…Quantification of signal intensity showed a 25% intensity increase using 4 M urea, whereas the SNR ratio was the same. Simard et al (2001) have previously shown that hybridization buffers with urea concentrations of 2-4 M urea performed as good as 50% formamide in reducing background hybridization in Northern blotting experiments, and Poulsen et al (2008) demonstrated in DNA microarray experiments that 4 M urea increased stringency of SSC buffers, resulting in increased specificity. The unchanged specificity of replacing formamide with urea was confirmed in the ISH assays by demonstrating that 2OMe + LNA probes with 2-bp mismatches against miR-124 (miR-124-2 mm), miR-138 (miR-138-2 mm), and miR-195 (miR-195-2 mm) without yRNA resulted in signal intensity decreases of 19-, 14-, and 16-fold, respectively, and decreases in SNR of 2.6-, 2.2-, and 6.2-fold, respectively, compared to the perfect match probe ( Supplementary Fig.…”
Section: Specificity In Hybridizationmentioning
confidence: 99%
“…Quantification of signal intensity showed a 25% intensity increase using 4 M urea, whereas the SNR ratio was the same. Simard et al (2001) have previously shown that hybridization buffers with urea concentrations of 2-4 M urea performed as good as 50% formamide in reducing background hybridization in Northern blotting experiments, and Poulsen et al (2008) demonstrated in DNA microarray experiments that 4 M urea increased stringency of SSC buffers, resulting in increased specificity. The unchanged specificity of replacing formamide with urea was confirmed in the ISH assays by demonstrating that 2OMe + LNA probes with 2-bp mismatches against miR-124 (miR-124-2 mm), miR-138 (miR-138-2 mm), and miR-195 (miR-195-2 mm) without yRNA resulted in signal intensity decreases of 19-, 14-, and 16-fold, respectively, and decreases in SNR of 2.6-, 2.2-, and 6.2-fold, respectively, compared to the perfect match probe ( Supplementary Fig.…”
Section: Specificity In Hybridizationmentioning
confidence: 99%
“…A truly high performance DNA biosensor should be able to discriminate as few as a single-base mismatches between different target DNA strains. Discrimination between matched and mismatched hybrids on the sensor surface can be achieved by employing various factors influencing hybridization efficiency, including target length and concentration, temperature, composition of hybridization buffer, post-hybridization stringency wash steps, and a combination of the factors [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Multisalinity gradient washing allows genotyping via parallel analysis of identical arrays treated with different stringency wash buffers. 26,27 In this case, each of the four lanes used to genotype a single patient was filled with one of the following four washing buffers: 2.0× SSC, 0.55× SSC, 0.10× SSC, and 0.035× SSC, all supplemented with 0.1% SDS, corresponding to 331.0, 91.6, 17.3, and 6.6 mM Na + , respectively. The lanes were filled for 1 min at room temperature to remove excess and unbound target.…”
Section: Genotyping In Mainstreammentioning
confidence: 99%
“…All signals were analyzed with GenePix Pro 6.1 (Molecular Devices, Sunnyvale, CA) and analyzed according to the multisalinity gradient washing method, which allowed for the use of probes with different washing buffer optima in the same microarray. 26,27 In Situ Hybridization An ISH assay was performed by attaching a device, called HistoFlex, 28 to a MainSTREAM system. In brief, HistoFlex encompasses a patterned PDMS insert, which upon sealing aligns microfluidic reaction chambers to tissue sections fixed on a microscope slide.…”
Section: Genotyping In Mainstreammentioning
confidence: 99%